2x^4 + x^3 − 8x^2 − 4x
= x ∙ (2x^3 + x^2 − 8x − 4)
= x ∙ (x^2 ∙ (2x + 1) − 4 ∙ (2x + 1))
= x ∙ (x^2 − 4) ∙ (2x + 1)
= x ∙ (x − 2) ∙ (x + 2) ∙ (2x + 1)
Thus the roots are:
x ∙ (x − 2) ∙ (x + 2) ∙ (2x + 1) = 0
⇒ [x = 0] or [x − 2 = 0] or [x + 2 = 0] or [2x + 1 = 0]
⇒ [x = 0] or [x = 2] or [x = −2] or [x = − 1/2]
Can you add the whole question I think it may be 6/4
-.25a-4=4
Add for on both sides
-.25a=8
Divide by -.25
A=
The angles of a triangle are right angles
90 = 1/3x + 8
82 = 1/3x
246 = x
Answer is B
If we are to write this equation in slope-intercept form, it will be in y = mx + b, where m is the slope of the line and b is the y intercept. We need then to find the slope of the line using 2 points on the line and filling in the slope formula to find the slope. One of the points we can use is (0, 3) which is also the y intercept. The y-intercept is found where x = 0. Where x = 0, y = 3. So b = 3. Now for the slope we will use (0,3) and (4,4):
. Using that m value and that b value we have the equation
. There you go!